Developmental Profiling of Tropomyosin Expression in Mouse Brain Reveals Tpm4.2 as the Major Post-synaptic Tropomyosin in the Mature Brain - Suchowerska, Alexandra K.; Fok, Sandra; Stefen, Holly; Gunning, Peter W.; Hardeman, Edna C.; Power, John; Fath, Thomas (Frontiers in Cellular Neuroscience, 2017)
Nerve cell connections, formed in the developing brain of mammals, undergo a well-programmed process of maturation with changes in their molecular composition over time. The major structural element at the post-synaptic specialization is the actin cytoskeleton, which is composed of different populations of functionally distinct actin filaments. Previous studies, using ultrastructural and light imaging techniques have established the presence of different actin filament populations at the post-synaptic site. However, it remains unknown, how these different actin filament populations are defined and how their molecular composition changes over time. In the present study, we have characterized changes in a core component of actin filaments, the tropomyosin family of actin-associated proteins from embryonal stage to the adult stage. Using, biochemical fractionation of mouse brain tissue, we identified the tropomyosin Tpm4.2 as the major post-synaptic tropomyosin. Furthermore, we found that different isoforms of the tropomyosin family of proteins have different dynamic properties in the post-synaptic compartment when expressed in cultured hippocampal neuronsage-related differences in the composition of tropomyosins at the post-synaptic compartment. Our findings will help to guide future studies that aim to define the functional properties of actin filaments at different developmental stages in the mammalian brain.